Evaluation techniques and improvements of adhesion strength for tin coating in tool applications: A review - Othman, M.F.; Bushroa, A.R.; Abdullah, W.N.R. (Taylor & Francis, 2015)
The adhesion between coating-substrate systems is an important factor in determining the performance and durability of coated engineering components. This paper reviews the microstructures and adhesion strength of titanium nitride (TiN) coating produced using two different processing methods: chemical vapor deposition and physical vapor deposition. Three methods to evaluate the adhesion strength of the coatings, namely the indentation test, laser spallation technique, and scratch test are presented and discussed in terms of their working principles, their advantages and disadvantages. The extrinsic and intrinsic factors influencing the adhesion strength of coating-substrate system, particularly for TiN coating, are also elaborated. The mechanisms and modes of coating failures in adhesion evaluation techniques are discussed with respect to the variation of coating-substrate system combination such as brittle, ductile, soft, and hard. Possible improvements on the adhesion strength of coating-substrate systems, focusing on the processing methods, compositions, and structures of coatings, are also reported.